Kemampuan Komunikasi Matematis Dalam Pendekatan Matematika Realistik di Sekolah Dasar - Nur Fauziah Siregar (AR-RIAYAH : Jurnal Pendidikan Dasar, 2019)
Mathematics has abstract objects. Students experience difficulties in mathematics because of their abstract character. The stage of the level of development of student thinking at the school level is still concrete, therefore we need an approach that is deemed good and appropriate that can overcome the problem or can bridge it with a realistic mathematical approach. This mathematics learning is oriented to experience in everyday life. Realistic Mathematics Approach in learning provides an opportunity for students to discover and reconstruct mathematical concepts, so students have an understanding of mathematical concepts. This learning can be used as an alternative to make mathematics learning more enjoyable which can affect students' mathematical communication. The mathematical communication process of good students can be a means to form effective and communicative learning, especially for elementary students who are in a concrete level of thinking.